ANALYZING THE IMPACT OF MARKETING INFORMATION ON THE PURCHASE DECISION OF ECO-FRIENDLY PRODUCTS - Tresnawati, Yuni; Bakhour, Alyssa Edwina Imad Khalid (International Journal of Social Science, 2025)
This research explores the impact of marketing information on eco-friendly product purchase decisions, focusing on young consumers, particularly vocational school students. With growing awareness of sustainability, consumers are increasingly considering environmental impact in their purchasing decisions. However, the effectiveness of marketing information in influencing eco-friendly product purchases remains uncertain. While some studies suggest green marketing shapes consumer behavior, others highlight product quality and trust in sustainability claims as more dominant factors. The study aims to analyze factors affecting consumer acceptance of sustainability claims, emphasizing how marketing strategies highlighting environmental aspects, social media, and peer influence shape decision-making. Expected outcomes include: (1) publication in a national accredited journal, (2) development of a green marketing education module for vocational students, (3) formulation of evidence-based green marketing strategies, and (4) intellectual property rights submission for the developed model. This research is positioned at Technology Readiness Level (TRL) 3–4, focusing on exploration and conceptual model development to be tested qualitatively. The results aim to provide a foundation for designing effective, evidence-based green marketing strategies that can be applied by both industries and educational institutions to encourage more responsible consumption.